Physiological Traits of Vanilla Plant (Vanilla planifolia Andrew) in Various Types of Shade Trees - Suryanti, Sri; Mawandha, Hangger Gahara; Oktavianty, Hera (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2024)
Vanilla plants are CAM species and are very sensitive to direct sunlight. Shade plants are crucial for mitigating the intensity of sunlight to protect vanilla plants. The physiological properties of vanilla plants under different shade trees were studied to understand how shade trees affect vanilla plants. The research applied a randomized completely block design with four groups. Planting was carried out using four shade plants, including Gliricidia sepium, Syzygium aromaticums, Erythrina variegata, and Leucaena leucocephala. Microclimate conditions such as temperature, humidity, and sunlight intensity were observed three times a day (morning, afternoon, and evening). Physiological observation parameters include chlorophyll A, chlorophyll B, total chlorophyll, proline, and relative water content. The research results showed that temperature, humidity, and intensity of sunlight varied depending on the type of shade plant. Types of shade plants significantly influence chlorophyll A content, chlorophyll B levels, total chlorophyll, proline, and relative water content. The conclusion indicated that the type of shade plant affects the microclimatic conditions of the vanilla plant, thereby influencing the physiological traits of the vanilla plant.